An unusual case of erythema annulare centrifugum involving face - Pekmezci, Erkin; Küçükodacı, Zafer; Kutlubay, Zekayi (Journal of Pakistan Association of Dermatologists, 2022)
Erythema annulare centrifugum (EAC) is a reactive figurate erythematous disease characterised by gyrate and annular plaques with erythema. The disease is generally known as involving the extremities and trunk, but sparing the face. We present a young male patient with recurring annular erythematous scaly lesions on his face, frequently in a year since four years, with no systemic involvement. Histologically, in addition to slight parakeratosis and spongiosis in the epidermis, there was superficial lymphocytic and histiocytic perivascular infiltration with the classic coat sleeve appearance of EAC in the dermis. Although uncommon, we suggest EAC should be considered in the differential diagnosis of relevant lesions on face